2010-2014 FARC TERRITORIAL EXPANSION (2018)
A FARC´s absolute territorial increase, with growth in 24 affected municipalities, becomes evident by observing their territorial presence, during the 2010-2014 period. This conclusion can be reached based on their actions and on the indicators of sabotage to economic infraestructure, terrorist acts, attacks against the Public Forces and crimes againts individual freedoms of civilians, such as kidnapping and extortion. All of this spite of the fact that this Guerrilla entered into a unilateral truce at the end of 2014 thes means that, from 207 territorial entities in 2010 their presence rose to 231 in 2014, wich, in percentage terms, means a 12% increase.